Drug Screening: Microfluidic Chip for Site‐Specific Neuropharmacological Treatment and Activity Probing of 3D Neuronal "Optonet" Cultures (Adv. Healthcare Mater. 10/2015). Issue 10 (July 2015) - Marom, Anat; Mahto, Sanjeev Kumar; Shor, Erez; Tenenbaum‐Katan, Janna; Sznitman, Josué; Shoham, Shy
<x xml:space="preserve">Abstract</x> On page 1478 S. Shoham and co‐workers introduce a "brain‐on‐a‐chip" microfluidic platform that hosts brain‐like 3D cultures ("optonets") whose activity and response to flowing drugs are recorded optically. Optonets are viable, optically accessible 3D neural networks whose characteristics approximate cortical networks. The results demonstrate the ability to monitor complex 3D activity patterns during extended site‐specific, reversible neuropharmacogical exposure, suggesting an interesting potential in drug screening.